Novel complex and hyperbolic forms to the strain wave equation in microstructured solids - Baskonus, Haci Mehmet; Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Springer, 2018)
This study applies the powerful sine-Gordon expansion method in acquiring some new solutions to the strain wave equation in micro-structured solids arising in mathematical physics. The strain wave equation in micro-structured solids is used in modelling wave propagation in micro-structured materials. We successfully acquire some new solitary wave solutions with hyperbolic function structure. By taking some suitable values of parameters involved in the solutions, we plot the 2D, 3D and contour graphs of all the obtained solutions in this study.
Keywords: The SGEM; Strain wave equation; Complex function; Hyperbolic function structure; Soliton solution